Estudo sobre a estratégia de negócios das empresas de autopeças no Brasil - Lelis, Ivan Farah (2008)
Auto parts Industry has an important participation in the Brazilian economy, with a turnover of US$ 29,8 billion/year, investing US$ 1,3 billlion/year and keeping 200.000 jobs. Despite the importance, the sector has been presenting negative profits. Some issues can collaborate with this bad result: incorrect business strategy, high cost of production, expending labor, cost of non quality, products replacement due to failure, etc. This paper will have focus on the first issue: business strategy in auto parts sector. This paper will identify and understand the business strategies used by auto parts companies and verify the respective effectiveness, concluding about the direct relationship between business strategy and financial results. The auto parts business strategies are evaluated according the theories of business strategies. This study involves a theoretical reference about auto parts, strategy, business strategy and finance. This theoretical reference is tested by interviews and searches into auto parts companies. At the end, a business strategy model is proposed to auto parts companies in Brazil